Pengaruh Penyaluran Kredit Dan Pendapatan Bunga Terhadap Profitabilitas Pada KPRI-UNM Di Kota Makassar - Rijal, Abd; Samsinar, Samsinar; Nurjannah, Nurjannah (JEKPEND: Jurnal Ekonomi dan Pendidikan, 2020)
This research aims to determine how much influence the credit lending and interest income to profitability on KPRI-UNM. The variables in this research were the distribution of credit (X1), interest income (X2) and profitability (Y). The population included all financial statements on KPRI-UNM in Makassar city and the sample in this research was financial statements on KPRI UNM for the last three years from 2016 until 2018. Data collection techniques used documentation and interviews. Data analysis techniques used Multiple Linear Regression Analysis, T-Test, and F-Test. The results of this research showed that the distribution of credit and interest income partially and simultaneously had a significant effect on profitability